Facile synthesis and lithium storage performance of tiny oxygen vacancy-enriched zinc manganate nanoparticles anchored on a reduced graphene oxide nanocomposite. (4th July 2022) - Zhong, Ming; Lin, Yasu; Yue, Bin; Li, Lingling; Han, Yuqi; Fu, Yongpeng; Zhang, Xiaobo
Abstract : Tiny ZnMn2 O4 anchored on an rGO nanosheet composite with rich oxygen vacancies was synthesized and applied as a lithium ion battery anode. Abstract : Searching for high-performance anode materials to alleviate the low capacity issue of commercial graphite is advantageous for the future development of lithium-ion batteries (LIBs). In this work, an oxygen vacancy-enriched zinc manganate anchored on a reduced oxide graphene (O-ZMO/rGO) nanocomposite was synthesized and used as an anode material in LIBs. As expected, the O-ZMO/rGO electrode delivers a high specific capacity of 1272.1 mA h g −1 after 100 cycles at a current density of 0.2 A g −1, an excellent rate capability, and long-term cycling stability of up to 700 cycles with 780.0 and 432.7 mA h g −1 capacity retained at high current densities of 1.0 and 2.0 A g −1, respectively. Oxygen vacancies provide abundant active sites and the small particle size of 10–20 nm shortens the diffusion distance of the Li + ions and transfer path of the electrons, while rGO enhance the electrical conductivity, thus contributing to the excellent lithium storage performance. Also, capacitance-controlled behavior was found to dominate the lithium ion transport kinetics during the electrochemical reaction process.